Grundtvig og censuren - Lundgreen-Nielsen, Flemming (Grundtvig-studier, 2007)
Grundtvig og censuren[Grundtvig and censorship]By Flemming Lundgreen-Nielsen For forty-six years of his life Grundtvig was engaged in a struggle for freedom of the press and freedom of speech. Over this period his attitude gradually changed. At the age of 21, he wanted not to abolish but to update the rigid and stem decree on the issue dating from 1799, his idea being that educated and scholarly orientated writers could serve as counsellors for the authorities instead of censors appointed by the police or by the Danish Chancellery (Ministry of the Interior).During a long middle period of his career as an author he time and again discussed and suggested models for setting up semi-official literary courts outside the normal court system, which could secure and improve the freedom of Danish writers and poets to no detriment of Danish society as such. In a lost libel suit in 1826 Grundtvig incurred life-long personal censorship which ran until 1837, when a revision of the relevant legal paragraph was realized. As a 67-year-old member of the first Danish democratic parliament, Grundtvig in 1850 advocated freedom of the press and of speech with as few limitations as possible. His winding way to this conclusion is followed through a series of his own texts with particular attention to two sources which have been overlooked by Grundtvig scholars, namely the censor suppressed third part of an essay on the freedom of religion (printed 1827, but not published until 1866) and a pamphlet issued in 1845 but never reprinted, opposing a proposed revision (1844) of the 1799 press ordinance. In the latter case, references to fragmentary manuscripts not included in Grundtvig’s final argumentation are added.